Achievement of Mathematical Problem-Solving Abilities of 4th Grade Students at SDN 02 Kajar through The Problem-Based Learning (PBL) Model: One-Sample T-Test Analysis - Khoirul Ana; Risma Hanim Mazida; Fauzul Muna; Fitriyah Amaliyah (Riemann: Research of Mathematics and Mathematics Education, 2025)
The mathematical problem-solving ability of IV grade students in plane geometry is still a concern that requires attention. Teachers, as educators, should apply varied learning models that can develop students' mathematical problem-solving skills. This research aims to determine whether the mathematical problem-solving abilities of IV grade students at SDN 02 Kajar in plane geometry using the Problem Based Learning (PBL) model can meet the minimum competency criteria (KKM) score or not. This study is quantitative research using a pre-experimental design method with a one-shot case study type, involving 15 fourth grade students at SDN 02 Kajar. Data collection techniques include mathematical problem-solving ability tests, observation, and interviews. The data obtained was then analyzed using the T-Test (one-sample t-test). The research results show that the achievement of mathematical problem-solving abilities through the Problem-Based Learning (PBL) model is equal to the minimum competency criteria (KKM) score, which is 75.